FEATURES OF AN INTEGRATED BANKING RISKS MANAGEMENT SYSTEM - Samchkuashvili, Nino; Dudauri, Tamar (Ecoforum Journal, 2022)
In the context of modern globalization and the financial crisis caused by the Covid pandemic, the integrated risk management system, which is conditioned and based on the international standard of Basel 3, has become widespread in the banking sector. Therefore, it is important to discuss the features and problems of the integrated banking risk management system, as well as to characterize its key elements and tools and to establish the procedures for its implementation in the banking system.